The effects of contact configuration and coating morphology on the tribological behaviour of tetrahedral amorphous diamond-like carbon (ta-C DLC) coatings under boundary lubrication. (3rd April 2019) - Mishra, Tanmaya; Nordin, Björn; Svanbäck, Daniel; Tervakangas, Sanna; Prakash, Braham
ABSTRACT: Tribological studies were carried out with tetrahedral amorphous diamond-like carbon (ta-C DLC) coatings, varying in thickness and roughness, using two different contact configurations lubricated with seven types of hydraulic oils. Tribopair of cast iron and ta-C coated steel were tested in both non-conformal and conformal, unidirectional sliding contacts. The friction and wear results were mainly affected by the thickness of the coating in the non-conformal contact and the surface roughness of the coating in the conformal contact. Tests done with mineral base oil containing rust inhibitor in the non-conformal contact and with Polyalphaolefins and synthetic ester base oils in the conformal contact resulted in the lowest friction while that with mineral base oil containing zinc resulted in high friction and counterface wear. The results highlight the interdependence of contact configuration, lubricant chemistry, coating's surface morphology and coating's thickness in determining the tribological behaviour of ta-C coatings under boundary lubrication.